Pelaksanaan Sewa Menyewa Kamar Indekos - Pulungan, Aminah Sari; Hasiah, Hasiah (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2021)
Leasing is a law of agreement consisting of two or more people who bind themselves to each other in which one party declares the ability to provide something and the other party binds itself in an agreement to help meet their respective needs. Likewise with the custom that applies in the community of Sihitang Urban Village Padangsidimpuan City which often rent boarding rooms.The problem in this thesis is how the community rents boarding rooms for student residences in Sihitang Urban Village Padangsidimpuan City and how does Fiqh Muamalah review the implementation of renting boarding rooms. The purpose of this thesis is to determine the implementation of boarding room renting in Sihitang Village Padangsidimpuan City and a review of the implementation of boarding room renting.The type of research is field research by using a qualitative descriptive research method, which is a research from various aspects to find the issue for which the answer is being sought.The results of this study are the implementation of leasing carried out by the people of Sihitang Village Padangsidimpuan City, contradicting the Fiqh Muamalah because it is not in accordance with the contract agreement at first resulting in broken promises boarding room renting reaserch is fialed custom that bording rooms, the problem in this is how the implementation from variose aspects to find the issue for which the bording room.